AIRBNB DI BALI: IDENTIFIKASI ULASAN ONLINE WISATAWAN ASING MELALUI METODE NETNOGRAPHY - Indra Bhaskara, Gde (Jurnal Master Pariwisata (JUMPA); Volume 05, Nomor 01, July 2018, 2018)
This research examines the emergence of Airbnb as a sharing economy in Bali, Indonesia. Airbnb is a company whose websites allows ordinary people to rent out their homes as tourist accommodation. The focus on this article is to examine the tourists’ reviews on some properties owned by local Balinese people. These properties are located in eight regencies and one municipality in Bali. These reviews were collected by using a non-participant netnogrpahy approach and the samples are those who stay at nine accommodations in Bali. The finding shows that instead of commenting and stressing about the rooms and supporting facilities that tourists obtain while staying in these accommodation, surprisingly they were emphasising their experiences in living with locals and the friendliness of local Balinese people. This article also highlights some issues of trust and reputation in the Airbnb business model.